THE LONG -TERM VARIATION OF ORGANIC CHARACTERISTICS IN DONGGANG RIVER USING EXCITATION EMISSION FLUORESCENT MATRIX (EEFM) INTEGRATED WITH PARALLEL FACTOR ANALYSIS (PARAFAC) - Cao, Jing; Chiu, Chun; Chen, Guan; Xiao, Zhong; Chen, Lih; Lai, Wen (MATTER: International Journal of Science and Technology, 2016)
In this study, Excitation Emission Fluorescent matrix (EEFM) integrated with Parallel factor analysis (PARAFAC) was applied to investigate the variation of organic property in Donggang River located in Southern Taiwan between Oct. 2010 and Oct. 2015. It reveals that both values of BOD5and COD had a closer proximity at twice samplings; however, the four main components in both samplings showed a different location of excitation and emission wavelengths. On Oct., 2010, EX/EM (percentage of area) of four components were respectively 320/410 nm (46 %), 370/460 nm (27 %), 290/350 nm (14 %) and 280/450 nm (13 %) mainly belonging to humic-like substance. Regrading to the result on Oct, 2015, 320/420 nm (29 %), 228,278/358 nm (29 %), 240/420(29 %) nm and 228/310 nm (14 %) were found attributed in amino organic substance with low excitation wavelength. On Oct.2015, the intensities of four main components in Cinsheda Bridge higher than those in other locations may be attributed with of heavily polluted source like piggery wastewater. For the partition of N-organic and C-organic, there had a significant change on both samplings.